Hemoglobin level and cardiothoracic ratio in children with chronic severe anemia - Fera Wahyuni; Muhammad Ali; Bidasari Lubis; Netty D. Lubuis; Tina Christina Tobing (Paediatrica Indonesiana, 2011)
Background Chronic severe anemia is known to increase cardiac output when the hemoglobin levels are < 7 g/dL for more than three months. Chronic severe anemia is also associated with a high incidence of cardiac enlargement and congestive heart failure.Objective To determine the relationship between hemoglobin level and cardiothoracic ratio in children with chronic severe anemia.Methods We conducted a cross-sectional study in Haji Adam Malik Hospital, Medan, Indonesia from October to December 2009. Subjects had chronic severe anemia and were aged 1 to 15 years. Hematological data was collected at the beginning of the study. The heart was considered enlarged if the cardiothoracic ratio (CTR) was greater than 50% (0.50) by chest roentgenogram. We used simple linear regression to analyze the relationship between hemoglobin and CTR values.Results Thirty subjects enrolled in our study. Their mean age was 115.7 months (SD 56.95). Hemoglobin levels ranged from 2.1 to 6.9 g/dL. The mean hemoglobin level and duration of anemia were 4.71 g/dL (SD 1.48) and 3.9 months (SD 0.70), respectively. Heart enlargement was observed in 23 patients (76.6%). The CTR ranged from 0.52 to 0.69, with a mean of 0.54 (SD 0.06). We found a significant correlation between CTR and hemoglobin levels with Pearson’s correlation coefficient, (r) = - 0.612 and P = 0.001.Conclusion Low hemoglobin levels significantly correlated with high CTR values in children with chronic severe anemia. [Paediatr Indones. 2011;51:262-5].